2021
DOI: 10.1016/j.heliyon.2021.e06723
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the computational domain size in CFD simulations of tall buildings

Abstract: Recently, there has been a growing interest in utilizing computational fluid dynamics (CFD) for wind resistant design of tall buildings. A key factor that influences the accuracy and computational expense of CFD simulations is the size of the computational domain. In this paper, the effect of the computational domain on CFD predictions of wind loads on tall buildings is investigated with a series of sensitivity studies. Four distinct sources of domain error are identified which include wind-blocking effects ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The domain size of external aerodynamic simulations can have a large impact on model accuracy, but also has a large impact on the number of cells in the mesh, and as a result computational effort. Abu-Zidan et al [49] aimed to optimize the domain size by comparing the results of many external simulations. They concluded that the previous recommendations by Franke et al [50] seemed overly conservative in most cases.…”
Section: D Domain Sizementioning
confidence: 99%
See 2 more Smart Citations
“…The domain size of external aerodynamic simulations can have a large impact on model accuracy, but also has a large impact on the number of cells in the mesh, and as a result computational effort. Abu-Zidan et al [49] aimed to optimize the domain size by comparing the results of many external simulations. They concluded that the previous recommendations by Franke et al [50] seemed overly conservative in most cases.…”
Section: D Domain Sizementioning
confidence: 99%
“…In this case, H refers to the tallest building height. Abu-Zidan et al [49] recommends 3H upstream, 3H downstream, 3H laterally, and 4H vertically. To remain conservative, the recommended domain size from Franke was used in this study, based on the height of the contactor units from the bottom of the domain.…”
Section: D Domain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…For a complex prefab structure, such as a tall building or a building that covers a large area, a load evaluation merely according to the loading standard may not be adequate. In such cases, a complete set of wind studies using a physical or virtual wind tunnel (using computational fluid dynamics) will be necessary to estimate the complete wind effects on the particular building [28,29]. The types of wind studies to consider are:…”
Section: Lateral Loads (Wind and Earthquake Loads)mentioning
confidence: 99%
“…It advantageously provides flexibility to change parametric design parameters without changing the existing system of the model. Moreover, the authors in [14] argued that the CFD's computational domain should have an optimized size to avoid uneconomic grids with large meshes. Their framework involves parametrizing the domain dimensions based on sensitivity analyses, where optimal values are obtained from acceptable levels of the following four domain errors: the wind-blocking effect, flow circulation, global venturi effect, and local venturi effect.…”
Section: Computational Fluid Dynamics Simulations For Typhoonsmentioning
confidence: 99%